2016
DOI: 10.1038/nn.4257
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive somatostatin interneurons contribute to excitotoxicity in neurodegenerative disorders

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are overlapping neurodegenerative disorders whose pathogenesis remains largely unknown. Here using TDP-43A315T mice, an ALS and FTD model with profound cortical pathology, we demonstrated that hyperactive somatostatin interneurons disinhibited layer 5 pyramidal neurons (L5-PN) and contributed to their excitotoxicity. Focal ablation of somatostatin interneurons efficiently restored normal excitability of L5-PN and alleviated neurodegeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 30 publications
6
140
1
Order By: Relevance
“…Specifically, we found that SST + interneurons were present at various levels of maturity at D54. SST cell death has been observed in mood disorders and dysfunctional SST interneurons have recently been shown to exacerbate cortical excitotoxicity in neurodegenerative disorders (Lin and Sibille, 2013;Zhang et al, 2016). Our analysis determined that several genes important for migration, synaptogenesis, axon outgrowth and ion channel function were differentially expressed by more mature interneurons.…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, we found that SST + interneurons were present at various levels of maturity at D54. SST cell death has been observed in mood disorders and dysfunctional SST interneurons have recently been shown to exacerbate cortical excitotoxicity in neurodegenerative disorders (Lin and Sibille, 2013;Zhang et al, 2016). Our analysis determined that several genes important for migration, synaptogenesis, axon outgrowth and ion channel function were differentially expressed by more mature interneurons.…”
Section: Discussionmentioning
confidence: 80%
“…In asymptomatic mutation carriers, SICI appears to be within normal limits, indicative of a normal level of cortical excitability [89,92], and suggesting that factors other than the inheritance of the genetic mutation are important to trigger the disease. Degeneration of inhibitory cortical interneurons along with hyperactivity of cortical excitatory interneurons appears to underlie the reduction of SICI and enhancement of ICF in ALS [94,95]. Given that seizures can affect TMS parameters [96], patients with ALS with seizure disorders were excluded from the above-discussed studies.…”
Section: Alsmentioning
confidence: 99%
“…Excess extracellular glutamate causes neuronal death by the disruption of intracellular organelles and aberrant proteolysis via ion-sensitive protease activation that results from excessive Ca 2ϩ influx following the overstimulation of Ca 2ϩ -permeable glutamate receptors (Hollmann et al, 1991;Verdoorn et al, 1991;Bano et al, 2005;Kwak and Weiss, 2006;Lewerenz and Maher, 2015). Accumulating evidence implicates excitotoxicity involvement in the pathogenesis of many neurodegenerative diseases including Alzheimer's disease, multiple sclerosis, Parkinson's disease, Huntington's disease, frontotemporal dementia (FTD), and amyotrophic lateral sclerosis (ALS; Kawahara et al, 2004;Kwak and Weiss, 2006;Mehta et al, 2013;Zhang et al, 2016), suggesting that these diseases may share excitotoxicity as a common pathogenic pathway. Thus, understanding the molecular mechanisms underlying chronic excitotoxic neuronal death is of critical importance for the treatment of many neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%